Adaptive fuzzy back-stepping control of drug dosage regimen in cancer treatment. (April 2018) - Nasiri, Hajar; Akbarzadeh Kalat, Ali
Highlights: The paper uses an adaptive fuzzy back-stepping control for a MIMO dynamical model of Cancer Treatment. In order to guarantee the asymptotic stability of the overall closed loop system, the controller is designed based on the Lyapunov theory. In spite of interaction between the variables of the system, each control signal is designed independently. Abstract: This paper presents an intelligent controller for MIMO cancer immunotherapy system. The treatment objective is obtaining a suitable scheduling scheme for drug dosage to decrease the tumor cells. Utilizing the back-stepping technique and property of universal approximation of the fuzzy systems, an adaptive fuzzy back-stepping controller for the MIMO cancer immunotherapy system is proposed. The response of closed-loop system is valid for any initial conditions and robust performance of the overall system for a wide range of the parameter uncertainties can be guaranteed. Simulation results clarify the efficiency of the suggested approach in the reduction of the number of tumor cells in the cancer model.